If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -26 + 5n = -5n + -6(1 + -1n) -26 + 5n = -5n + (1 * -6 + -1n * -6) -26 + 5n = -5n + (-6 + 6n) Reorder the terms: -26 + 5n = -6 + -5n + 6n Combine like terms: -5n + 6n = 1n -26 + 5n = -6 + 1n Solving -26 + 5n = -6 + 1n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. -26 + 5n + -1n = -6 + 1n + -1n Combine like terms: 5n + -1n = 4n -26 + 4n = -6 + 1n + -1n Combine like terms: 1n + -1n = 0 -26 + 4n = -6 + 0 -26 + 4n = -6 Add '26' to each side of the equation. -26 + 26 + 4n = -6 + 26 Combine like terms: -26 + 26 = 0 0 + 4n = -6 + 26 4n = -6 + 26 Combine like terms: -6 + 26 = 20 4n = 20 Divide each side by '4'. n = 5 Simplifying n = 5
| S-2s+3s-4s+5s=s+100 | | 9x+5(4+8x)= | | 2r^2+15r-19=0 | | 12+x=1 | | 4(2x+3)+3x=45 | | 6r+2=r+12 | | 8x+20-2x=40 | | 8q+8q= | | 4x-2y=6 | | 7(y+3)=98 | | 3a-13=19 | | Y-7=10 | | x+2x+3x+4x=10+20+30+40 | | 8p+p= | | 5=5(x-5)+2-4x | | 3(x+4)+6x=66 | | 6y+6+8y-6= | | 6x+5=-(x-33) | | 11r-5r+6r=168 | | 4x+10=2x+14 | | 8x+30=8x+3 | | 3+5j+4= | | 25=3(5-2y)+5 | | 4x+34=14x-76 | | x^2+2x=80 | | 7x+y=-33 | | 3x^2-18x+24=0 | | -6(-2+3g)= | | 11x-15=8x+3 | | 3(2x+1)+5=25 | | 3x=x+1 | | 12j=16j-128 |